2019
DOI: 10.1101/764787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic interrogation of the burden and transmission of multidrug-resistant pathogens within and across hospital networks

Abstract: BackgroundMultidrug-resistant organisms (MDROs) disproportionately affect hospitalized patients due to the combination of comorbidities, frequent antimicrobial use, and in-hospital MDRO transmission. Identification of MDRO transmission by hospital microbiology laboratories is difficult due to limitations of existing typing methods.MethodsWe conducted a prospective multicenter genomics implementation study (8 hospitals, 2800 beds) from 24thApril to 18thJune 2017 in Melbourne, Australia. Clinical and screening i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…To broaden the exploration of low-level oxacillin adaptation, we investigated a collection of 490 previously described mec -negative S. aureus clinical isolates obtained from two cohort studies of S. aureus bacteremia ( 4 , 32 ) and a genomic study of multidrug-resistant microorganisms ( 33 ). The majority of the isolates had a low MIC (median, 0.38 mg/liter; interquartile range [IQR], 0.19 to 0.38 mg/liter); however, 40 of them (∼8%) had reduced oxacillin susceptibility (MIC of ≥1 mg/liter) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To broaden the exploration of low-level oxacillin adaptation, we investigated a collection of 490 previously described mec -negative S. aureus clinical isolates obtained from two cohort studies of S. aureus bacteremia ( 4 , 32 ) and a genomic study of multidrug-resistant microorganisms ( 33 ). The majority of the isolates had a low MIC (median, 0.38 mg/liter; interquartile range [IQR], 0.19 to 0.38 mg/liter); however, 40 of them (∼8%) had reduced oxacillin susceptibility (MIC of ≥1 mg/liter) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We selected 490 mec -negative isolates from a combined collection of S. aureus bacteremia isolates ( 4 , 32 ), supplemented with high-oxacillin-MIC isolates (MIC of ≥1 mg/liter) from a prospective genomic study of multidrug-resistant microorganisms ( 33 ). Whole-genome sequencing, quality control, resistome, and multilocus sequence type analysis were performed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…We defined probable strain transmission events on the basis of chromosomal SNVs (see Methods, Figure 3b-c ). Using a threshold of ≤20 SNVs for transmission of 3GCR-GN (based on recent studies [10,13,14,28]) we identified six putative 3GCR-GN transmission clusters each involving 2-3 patients (maximum 8 SNVs, Table 2 ). With a single exception, all patients within clusters were epidemiologically linked (overlapping ICU stays or ≤14 days between stays).…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of VRE pairwise SNVs is more complex because several healthcare-associated lineages are known to be circulating in Melbourne and the regional hospital network. Consequently, it is not uncommon to find near-identical isolates in patients from different wards, hospitals or cities without epidemiological links [7,8,13]. We therefore used a more conservative threshold of ≤3 SNVs to define putative recent VRE transmissions (based on empirical distribution, see Figure S3 ), which identified four clusters of 2-7 patients each ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation